The status of Arctic charr, Salvelinus alpinus (L.), in southern Scotland: a cause for concern - Maitland, Peter S. (1992)
The objective of this article is to review the populations of Arctic charr in the south of Scotland which have become locally extinct, and the reasons for their demise. In the British Isles, the Arctic charr in individual lakes have been isolated from each other for thousands of years and have developed a variety of phenotypic characteristics which are probably genetically based. About 200 populations of Arctic charr have been recorded from different parts of the British Isles: approximately 12 in England, 50 in Ireland, 175 in Scotland and four in Wales. The threats to charr from acidification, afforestation, engineering schemes, angling and fish farming are assessed, and the establishment of new populations is proposed as a method of replacing extinct stocks or providing an additional safeguard for valuable stocks in threatened waters.